Assessment of pulmonary arterial enhancement on CT pulmonary angiography using a leg vein for contrast media administration. Issue 49 (December 2017) - Kim, Cherry; Lee, Choong Wook; Hong, Gil-Sun; Kim, Gihong; Lee, Ki Yeol; Kim, Sung-Soo
Abstract : Abstract: The purpose of our study was to compare pulmonary artery (PA) enhancement according to venous routes of contrast media (CM) administration in patients who underwent CT pulmonary angiography (CTPA) in the emergency department (ED). This retrospective study reviewed the CTPAs of 24 patients who administered CM via leg veins (group A) and 72 patients via arm veins (group B) with age and gender matching at a ratio of 1:3. Clinical data, aorta attenuation (Aoatten ), and PA attenuation (PAatten ) were compared between group A and B. Each group was subcategorized into diagnostic and nondiagnostic CTPA subgroups, with a threshold of 250 HU at the PA. Then, clinical data, rates of pulmonary embolism (PE), and right ventricle (RV) strain were compared. In group A, the relationship between the narrowest suprahepatic IVC area (IVCarea ) and the attenuation ratio of the RV to the intrahepatic IVC (RV/IVCatten ) was evaluated. Aoatten (236.6 HU vs 293.1 HU, P   <  .001) and PAatten (266.7 HU vs 321.4 HU, P   =  .026) were significantly lower in group A than in group B. The proportion of nondiagnostic CTPA was significantly higher in group A than in group B (58.3% vs 19.4%, P  = .001). In the subgroup analysis in of group A, patients with a nondiagnostic CTPA were significantly younger (55.3 years vs 68.6 years, P   =  .026) and showed a significantly lower incidence rate of PE (14% vs 70%, P  = .01) than patients with a diagnostic CTPA. However, the radiological diagnostic rate of RV strain was comparable between patients with nondiagnostic and diagnostic CTPA. In group A, IVCarea and RV/IVCatten were positively correlated, with a correlation coefficient of 0.430 ( P   <  .036). In conclusion, administration of CM through the leg veins increases the nondiagnostic CTPA rate, reducing the detection rate of PE. When CM is injected via the leg veins, the degree of PA enhancement is related with to the diameter of the suprahepatic IVC; therefore, adjustment of respiratory maneuvers may be needed to promote IVC flow into the right cardiac chamber, and to improve PA enhancement.